Learn AWS automation with Boto3, Python, and Lambda functions (Packt Publishing, 2021)
Gain expertise with hands-on real-time use cases using Boto3 and Lambda functions for automating their workloads.The objective of the course, AWS Automation with Boto3, Python, and Lamba Functions, is to cover the core concepts of Boto3 and Lambda. In most of the cases, Boto3 works along with Lambda and that's the reason we combine Boto3 and Lambda into one course. We have divided the course into two parts to get more clarity about Boto3 and Lambda. Part 1 is about how to write and execute Python Boto3 on our local server or any OS. Part 2 is about writing and executing Python Boto3 in Lambda with different triggering methods. Boto3 is the name of the Python SDK for AWS or Boto3 is the Python module to work with AWS services using Python scripts. It allows you to create, update, and delete AWS services from our Python scripts without opening AWS management console through the browser; we can execute these Python Boto3 scripts either from our local server or using AWS Lambda service. In this course, we will see how to implement and execute Python Boto3 scripts on our local server; then, we will move on with AWS Lambda service. Boto3 is built on top of the Botocore module. We will also explore the different types of Boto3 sessions and the concepts of Boto3 to write Python scripts for AWS automation. By the end of this course, you will get the knowledge to apply different concepts of Boto3 and Lambda for different AWS services.